Airway management in Ludwig's angina - a challenge: case report - Fellini,Roberto Taboada (2017)
Abstract Background Ludwig's angina (LA) is an infection of the submandibular space, first described by Wilhelm Frederick von Ludwig in 1836. It represents an entity difficult to manage due to the rapid progression and difficulty in maintaining airway patency, a major challenge in medical practice, resulting in asphyxia and death in 8-10% of patients. Objective Describe a case of a patient with Ludwig's angina undergoing surgery, with emphasis on airway management, in addition to reviewing the articles published in the literature on this topic. Case report Male patient, 21 years, drug addict, admitted by the emergency department and diagnosed with LA. Difficult airway was identified during the anesthetic examination. In additional tests, significant deviation from the tracheal axis was seen. Undergoing bilateral thoracoscopic pleural drainage, we opted for airway management through tracheal intubation using fiberoptic bronchoscopy, and balanced general anesthesia was proposed. There were no complications during the surgical-anesthetic act. After the procedure, the patient remained intubated and mechanically ventilated in the intensive care unit. Conclusions Airway management in patients with Ludwig's angina remains challenging. The choice of the safest technique should be based on clinical signs, technical conditions available, and the urgent need to preserve the patient's life.